The Sublime Excess of the American Landscape : Dances with Wolves and Sunchaser as Healing Landscapes - Natali, Maurizia (Cinémas)

(untitled) (Cinémas, 2001)
ABSTRACTThe author analyses the landscapes of the films Dances with Wolves by Kevin Costner and Sunchaser by Michael Cimino, considering them as "theatres of memory" in which numerous arts are "remediated" for the screen. Here the conflictual relationship Americans have with the native Other as an "obstacle" to the doctrine of Manifest Destiny is projected onto its landscapes, staged and recomposed on them. In Dances with Wolves, the hero's new name suggests the loss of his American subjectivity, his links with the natives and a revisionist version of Manifest Destiny. In Sunchaser also the east-west dynamic illustrates the hope for rebirth and rebellion. Here the "pyramidal sublime" of the mountain is the signifier that motivates the road movie of the two heroes. The sequence in which they ride on horses together with the natives condenses the landscape culture's various strata. Film landscapes are a part of the contemporary archive of remediations : they instigate a conflictual memory and produce emblems of cinematic iconological "excess."